Small savings mobilization and Asian economic development : the role of postal financial services - Scher, Mark J.; Yoshino, Naoyuki, 1950- (Online access with DDA: Askews (Economics), 2004)
Postal savings systems in developing Asian countries play a significant role in social and economic development. This book examines the postal financial systems of 20 countries, and covers topics including savings product development, investing mobilized funds, and utilizing financial technology.